Pengembangan Sistem Pemesanan e-Ticket pada Transportasi Umum di Provinsi Aceh - Naila Ilmi; Iskandar Zulkarnaini; Riyadhul Fajri (Jurnal Ilmu Komputer Aceh, 2026)
The rapid development of information technology has encouraged digital transformation in transportation services, including ticket reservation systems. In Aceh, land transportation ticket booking is still frequently handled manually, causing inefficiency in schedule distribution, seat management, transaction recording, and ticket validation. This study aims to develop a web-based e-ticket booking system for public transportation in Aceh with Sultan Loket Matang as the case study. The system is designed to support direct booking by passengers as well as booking through registered agents, especially for users with limited access to official ticket counters. The study applies a Research and Development approach with the Waterfall model, consisting of requirements analysis, system design, implementation, and testing. The developed system provides user registration, login, schedule and route search, seat selection, simulated digital payment, electronic ticket generation, and QR Code-based validation. The results indicate that the system can improve booking efficiency, facilitate integrated transportation data management, and reduce the possibility of ticket duplication through digital verification. Therefore, the proposed system can serve as an alternative solution for improving public transportation services in Aceh